Human Phaeohyphomycotic Osteomyelitis Caused by the Coelomycete Phomopsis Saccardo 1905: Criteria for Identification, Case History, and Therapy - Sutton, Deanna A. (American Society for Microbiology, 1999)
The Sphaeropsidales, coelomycetous fungi producing asexual conidia within enclosed conidiomata (pycnidia), are saprobic on numerous vascular plants. Despite their ubiquitous nature, only a limited number of genera have been documented as causing human disease. We report what we believe to be the first human case of osteomyelitis due to a Phomopsis species in a chronically immunosuppressed female. The patient developed a subcutaneous abscess on the distal phalanx of the right fourth finger complicated by osteomyelitis. Operative specimens revealed fungal hyphae and a pure culture of mould. The patient was treated with a 6-month course of itraconazole. At 16 months of follow-up, she remained free of recurrence. Phomopsis species differ from the similar, more frequently reported Phoma species by having immersed, thick-walled, multiloculate conidiomata and by the production of alpha (short, ellipsoidal) and beta (long, filamentous) conidia.